Tantangan Komunikasi dan Pengaruhnya Terhadap Kepuasan Pernikahan Pada Pasangan Long Distance Marriage - Bungawali, Andi Nahliah (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. Marriage and living together with a loved one are everyone's dreams. However, some couples must live separately due to various reasons such as education, work, and other factors. This research examines the role of communication and marital satisfaction in couples experiencing long-distance marriage. The article search was conducted by searching for journals discussing long-distance marriage, resulting in 10 journals from 54 journals analysed through meta-synthesis. The research found that effective communication patterns and marital satisfaction are crucial to maintaining long-distance relationships. Communication issues can lead to conflicts and ultimately divorce if not properly managed. This study provides insights into maintaining relationship quality through effective communication strategies and understanding factors contributing to marital satisfaction in long-distance marriages. Keywords: Long-distance marriage; marital satisfaction; communication